Estradiol Modulates bcl-2 in Cerebral Ischemia: A Potential Role for Estrogen Receptors - Dubal, Dena B. (J Neurosci, 1999)
We have shown that physiological levels of estradiol exert profound protective effects on the cerebral cortex in ischemia induced by permanent middle cerebral artery occlusion. The major goal of this study was to begin to elucidate potential mechanisms of estradiol action in injury. Bcl-2 is a proto-oncogene that promotes cell survival in a variety of tissues including the brain. Because estradiol is known to promote cell survival via Bcl-2 in non-neural tissues, we tested the hypothesis that estradiol decreases cell death by influencingbcl-2 expression in ischemic brain injury. Furthermore, because estradiol may protect the brain through estrogen receptor-mediated mechanisms, we examined expression of both receptor subtypes ERα and ERβ in the normal and injured brain. We analyzed gene expression by RT-PCR in microdissected regions of the cerebral cortex obtained from injured and sham female rats treated with estradiol or oil. We found that estradiol prevented the injury-induced downregulation of bcl-2expression. This effect was specific to bcl-2, as expression of other members of the bcl-2 family (bax, bcl-x(L), bcl-x(S), and bad) was unaffected by estradiol treatment. We also found that estrogen receptors were differentially modulated in injury, withERβ expression paralleling bcl-2expression. Finally, we provide the first evidence of functional ERβ protein that is capable of binding ligand within the region of the cortex where estradiol-mediated neuroprotection was observed in cerebral ischemia. These findings indicate that estradiol modulates the expression of bcl-2 in ischemic injury. Furthermore, our data suggest that estrogen receptors may be involved in hormone-mediated neuroprotection.